The clinical characteristics and outcomes of patients with pulmonary hypertension in association with hyperthyroid state: A systematic review - Fateen Ata (12217764) (2022)
Background Pulmonary hypertension (PHTN) may occur in thyroid disorders, especially in hypothyroidism. However, there is increasing evidence of PHTN in hyperthyroidism (HTH). The etiology, clinical course, management, and factors associated with outcomes of PHTN in the setting of HTH are unascertained. This systematic review consolidates available evidence on patients with HTH who developed PHTN. Methods We conducted a systematic review on English articles from PubMed, Scopus, and Google Scholar reporting PHTN in patients with hyperthyroidism. Data were analyzed and reported in Microsoft Excel 2020, SPSS version 26, and Jamovi version 1.2. Results We identified 589 patients with PHTN in the setting of HTH. Etiologies included Grave disease 66.7%), toxic multinodular goiter (TMNG) (16.8%), drug-induced HTH (0.3%), thyroiditis(0.8%), and toxic adenoma(0.1%). Most patients did not receive any specific management for PHTN and were managed by antithyroid treatment (97.4%). Outcomes of PHTN were reported in 181 patients, with a 94% recovery rate. Pulmonary artery pressures (PAP) before and after HTH management ranged from 22.5 to 75 mm Hg and from 24 to 50 mm Hg, respectively. Outcome analysis performed on data from case reports and series with individually identifiable data revealed a 67.6% female preponderance. An estimated 73.5% of the patients had PHTN at the initial presentation of HTH, which was associated with a better resolution rate of PHTN(OR: 12, P-value: 0.048). TRAB was positive in 47% patients with no clinical difference in outcomes. antiTG AB was reported positive in 29.4%, all of whom had an improvement, compared to an 83.3% improvement rate in those with negative antiTG AB. Various etiologies and treatments did not have any significant differences in the outcome of PHTN. Conclusions PHTN can be present at the initial diagnosis of HTH, which is associated with better outcomes of PHTN. There is a clear female preponderance in the development of PHTN. However, resolution rates seem to be better in males. Although TRAB is associated with the development of PHTN, it does not seem to affect the outcomes. PHTN in patients with HTH does not need any specific management, with >90% resolution with antithyroid therapy. Whether any specific antithyroid therapy has a better outcome in PHTN needs to be explored prospectively. Other Information Published in: Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1097/md.0000000000029832